Leitura, leituras breves contributos para novas abordagens - João Lopes Teixeira (Universidade do Minho, 2002)
This text begins with an overview of the main findings of reading practices surveys in the Portuguese social formation, then some hypothesis concerning new research perspectives in association with possible meanings for reading practices are discussed. It concludes with some guidelines for a «complex» cultural practice of reading promotion.